Nicky and the Big, Bad Wolves - Gorbachev, Valeri (New York North-South Books, 1998)
Nightmares are scary for children -- and for little rabbits, too. The illustrations turn Nicky's scary night into a rollicking, reassuring bedtime book that's just right for restless sleepers.
Keywords: Nightmares - Fiction; Rabbits - Fiction; Wolves - Fiction